Maternal heart rate during the first 48 h postpartum: a retrospective cross sectional study. (November 2016) - Samways, Jack W.; Vause, Sarah; Kontopantelis, Evangelos; Eddleston, Jane; Ingleby, Sarah; Roberts, Anna; Clarke, Bernard
Abstract: Objectives: 1) Describe the distribution of heart rate in the first 48 h postpartum in women with no evidence of sepsis, anaemia or haemorrhage. 2) Investigate the relationship between postpartum heart rate and other maternal factors. Study design: A retrospective cross-sectional study of postpartum women who delivered between July 2012 and June 2015 in a tertiary hospital. Data was analysed from the local maternity system and electronic vital signs database. The main outcome measures: Heart rate at 6, 12, 24 and 48 h postpartum. Results: Data were obtained on 11401 women. After exclusion of women with possible sepsis, anaemia or haemorrhage, 7627 heart rate readings from 5164 women were analysed. Mean heart rate (+2SD/+3SD) at 6 h was 83.6 (108.2/120.6), 12 h 84.5 (109.4/121.9), 24 h 85.4 (110.4/122.9), and 48 h 84.3 (109.7/122.4). There was statistical correlation of post partum heart rate with body mass index (BMI), age and discharge haemoglobin. Conclusion: This study describes the distribution of maternal heart rate in the early postpartum period, in women with no evidence of sepsis, anaemia or major haemorrhage. This will facilitate identification and appropriate investigation of women with abnormal heart rates. Although correlation with BMI, age and discharge haemoglobin was demonstrated, the differences were small and not clinically meaningful. Further work investigating the relationship between postpartum heart rate and poor maternal outcomes is required.